Comparison of the Effectiveness of Career Path Development Parenting with Attachment-Based Parenting on Mothers' Mental Health and Parenting Orientation - Heydari, Raha; Yousefi, Zahra; Mahdad, Ali (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The aim of this research was to compare the effectiveness of career path development parenting training with attachment-based parenting training on mothers' mental health and parenting orientation.Materials and Methods: The research method was quasi-experimental with a pretest, posttest, and follow-up design involving three groups; the statistical population included all mothers with elementary school children. The sample consisted of 60 mothers who were selected purposefully based on inclusion and exclusion criteria and were assigned to two training groups and one control group. The research instruments were the General Health Questionnaire (GHQ) by Goldberg and Hiller (1972) and the Parenting Orientation Questionnaire (Yousefi, 2021). While the control group was on a waiting list, the experimental groups received the educational interventions. The collected data were analyzed at both descriptive (mean and standard deviation) and inferential levels (repeated measures ANOVA). Calculations were performed using SPSS software.Findings: The results showed that, among career path development parenting and attachment-based parenting, only career path development parenting style was effective in improving mothers' mental health and parenting orientation.Conclusion: Thus, it can be concluded that career path development parenting is effective in enhancing the mentioned parenting constructs.